2014
DOI: 10.4103/1673-5374.128240
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of inhibiting the activation of glial cells on retinal synaptic plasticity

Abstract: Various retinal injuries induced by ocular hypertension have been shown to induce plastic changes in retinal synapses, but the potential regulatory mechanism of synaptic plasticity after retinal injury was still unclear. A rat model of acute ocular hypertension was established by injecting saline intravitreally for an hour, and elevating the intraocular pressure to 14.63 kPa (110 mmHg). Western blot assay and immunofluorescence results showed that synaptophysin expression had a distinct spatiotemporal change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The number and distribution of excitatory glutamatergic and inhibitory gamma-aminobutyric acid (GABAergic) neurons in the human central nervous system must be precisely controlled. The imbalance or loss of glutamatergic and GABAergic neurons is observed in many nervous system disorders, such as Alzheimer’s disease 11 , age-related macular degeneration 12 and mental retardation 13 . Although Alzheimer’s disease affects many types of neurons, including non-glutamatergic interneurons and cholinergic projection neurons, as well as glia, it is still desirable to understand the molecular mechanisms that govern glutamatergic neuron differentiation and to develop a consistent and reproducible glutamatergic neuron source for elucidating the aetiology of neurological disorders.…”
mentioning
confidence: 99%
“…The number and distribution of excitatory glutamatergic and inhibitory gamma-aminobutyric acid (GABAergic) neurons in the human central nervous system must be precisely controlled. The imbalance or loss of glutamatergic and GABAergic neurons is observed in many nervous system disorders, such as Alzheimer’s disease 11 , age-related macular degeneration 12 and mental retardation 13 . Although Alzheimer’s disease affects many types of neurons, including non-glutamatergic interneurons and cholinergic projection neurons, as well as glia, it is still desirable to understand the molecular mechanisms that govern glutamatergic neuron differentiation and to develop a consistent and reproducible glutamatergic neuron source for elucidating the aetiology of neurological disorders.…”
mentioning
confidence: 99%
“…In the current study, we observed the upregulation of presynaptic proteins without the accompanying changes in postsynaptic proteins in primary mixed cultures exposed to EHP for 2 h. That means that EHP only induced presynaptic protein changes, but no intact and functional synapses were formed[ 13 , 22 ]. However, protein synthesis function is highly dependent on mitochondrial energy production, and abnormal synthesis function may lead to energy deficits in cells and increased apoptosis[ 52 ].…”
Section: Discussionmentioning
confidence: 73%
“…In many neuropathic and nervous injury states, glia cells can be activated, characterized by increased proliferation and glial fibrillary acidic protein (GFAP) expression[ 20 , 21 ]. Our previous study also demonstrated that retinal synaptic changes are accompanied by activation of macroglia cells (astrocytes and Müller cells) following acute elevated IOP[ 22 ]. Meanwhile, the already increased expression of SYN was decreased when the activated macroglia cells were inhibited by fluorocitrate.…”
Section: Introductionmentioning
confidence: 99%
“… Porciatti and Ventura (2012) used the concept of neural plasticity to simulate the reversible/inducible changes in the PERG during the critical period (stage of retinal ganglion cell dysfunction), which precedes their death. Zhou et al (2014) suggested that retinal glial cell activation induced by acute high intraocular pressure may cause the process of retinal synaptic plasticity through affecting the expression of synaptophysin and other synaptic proteins. In the rat model of acute ocular hypertension, the increase in expression of synaptophysin across the retina was observed from the inner to the outer plexiform layer.…”
Section: The Plasticity Of the Brain And Sensory Experiencementioning
confidence: 99%